Testing a JD-R based SEM model of person–organization fit, person–job fit, and perceived organizational support toward employee performance: the mediating role of engagement in jakarta’s banking sector - Susanty, Rasty; Prasetyo, Lukman; Adityo, Agustinus; Prasetya, Agustian Budi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study aims to analyze the influence of Person-Organization Fit (P-O Fit), Person-Job Fit (P-J Fit), and Perceived Organizational Support (POS) on employee performance, as well as to evaluate the mediating role of job satisfaction among permanent employees in the banking sector in Jakarta. The research uses a quantitative explanatory approach with a survey method, involving 300 bank employees in Jakarta as respondents. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with 5,000 bootstrap resampling. The results show that POS has both a direct and indirect significant effect on employee performance through job satisfaction. P-O Fit directly affects performance but does not significantly influence job satisfaction. Conversely, P-J Fit significantly affects job satisfaction but does not have a direct impact on performance. Job satisfaction is proven to be a significant mediator in the relationships between P-J Fit and POS with performance. These findings highlight the importance of organizational support and job fit in enhancing employee satisfaction and performance. The practical implication of this study suggests that human resource strategies in the banking sector should focus on increasing job satisfaction through alignment and organizational support approaches as a strategic effort to improve employee performance.